2015
DOI: 10.2141/jpsa.0140009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Whole-Grain Paddy Rice on Growth Performance, Oxidative Stress and Morphological Alterations of the Intestine in Broiler Chickens Exposed to Acute and Chronic Heat Stress

Abstract: We have previously shown that, under thermoneutral conditions, the growth performance of chicks fed a ricebased diet containing 6% soybean oil [metabolizable energy (ME): 2,800 kcal/kg] for 28 days was comparable to that obtained with a corn-based diet containing 6% soybean oil (ME: 3,100 kcal/kg). However, there is no information available concerning how such diets compare with respect to growth performance under heat stress conditions. The present study was therefore conducted to clarify differences in dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…NPY has been considered as a food-intake regulator; however, our studies have revealed a novel role for NPY in reducing stress and body temperature in chicks under heat stress. As heat stress is a serious concern for the present and future poultry industry, our and other studies (Furukawa et al, 2015;Nanto et al, 2015;El-Deep et al, 2016;Mahmoudi et al, 2018) will contribute to overcome this serious, global challenge.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…NPY has been considered as a food-intake regulator; however, our studies have revealed a novel role for NPY in reducing stress and body temperature in chicks under heat stress. As heat stress is a serious concern for the present and future poultry industry, our and other studies (Furukawa et al, 2015;Nanto et al, 2015;El-Deep et al, 2016;Mahmoudi et al, 2018) will contribute to overcome this serious, global challenge.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…To offset this demand, several studies demonstrated that the rice, including brown rice, shows potential for use as a substitute for maize in poultry feed (Honda et al, 2011;Sittiya et al, 2011;Nanto et al, 2015Nanto et al, , 2016. In Korea, a search for local sources of poultry feed has been underway to replace expensive imported feed stuffs, mainly maize and soybeans.…”
Section: Introductionmentioning
confidence: 99%
“…Protein carbonyl content in Pectoralis superficialis muscles was measured as a major marker of oxidative stress as previously described (Nanto et al 2015). The protein carbonyl content was determined by derivatization with 2,4-dinitrophenylhydrazine (DNPH) (Levine et al 1990;Dalle-Donne et al 2003).…”
Section: Determination Of Oxidative Stressmentioning
confidence: 99%